2018
DOI: 10.1002/brb3.1171
|View full text |Cite
|
Sign up to set email alerts
|

Chronic idiopathic axonal polyneuropathy: Prevalence of pain and impact on quality of life

Abstract: Background and AimChronic idiopathic axonal polyneuropathy (CIAP) is a term describing axonal neuropathies of insidious onset, with slow or no progression of the disease over at least 6 months and with no etiology being identified despite appropriate investigations. We aimed to establish the prevalence of pain in patients with CIAP and investigate the impact of pain on quality of life (QoL).MethodsAll consecutive patients with CIAP attending a specialist neuropathy clinic were invited to participate. Pain was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 26 publications
(26 reference statements)
0
13
0
Order By: Relevance
“…It is slowly progressive, insidious, with no identifiable aetiology despite extensive diagnostic work-up [3, 75]. CIAP is correlated with a worse QoL in the energy/fatigue domain, the emotional well-being domain, and the general health perception domain [8]. In a small, open-label trial, lidocaine (5% patches) was found to significantly improve pain and QoL in CIAP [76].…”
Section: Resultsmentioning
confidence: 99%
“…It is slowly progressive, insidious, with no identifiable aetiology despite extensive diagnostic work-up [3, 75]. CIAP is correlated with a worse QoL in the energy/fatigue domain, the emotional well-being domain, and the general health perception domain [8]. In a small, open-label trial, lidocaine (5% patches) was found to significantly improve pain and QoL in CIAP [76].…”
Section: Resultsmentioning
confidence: 99%
“…Pain is a common and disabling symptom that is prevalent in patients suffering from peripheral neuropathy (PN). Pain adds to the burden of the disease and has an additional and significant negative impact to patients’ quality of life [2, 3].…”
Section: Introductionmentioning
confidence: 99%
“…Sensory symptoms that are seen in PN include tingling, pins and needles sensations, numbness, tightness, burning, itchiness, sensory ataxia and pain. The latter is very prevalent as it affects up to two thirds of patients, independently of aetiology [10][11][12].…”
Section: Introductionmentioning
confidence: 99%